High-dose anabolic implants are not all the same for growth and carcass traits of feedlot steers: A Meta-Analysis - Christopher D Reinhardt (Kansas Agricultural Experiment Station Research Reports, 2014)
The beneficial effects of anabolic implants with respect to feedlot performance and carcass weight are nearly unequivocal. Although individual prospective studies may have concluded that there are no significant differences between implant dosages, modern production economics demand that any differences, however small, must be gleaned if they are real. The objective of this study was to conduct a meta-analysis of existing data from peer-reviewed as well as industry sources to compare the effects of different doses of anabolic implants on feedlot performance and carcass traits of steers.
Keywords: Cattlemen' s Day; 2014; Kansas Agricultural Experiment Station contribution; no. 14-262-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1101; Beef Cattle Research; 2014 is known as Cattlemen' s Day; Anabolic implants; Feedlot cattle; Carcass traits; Steers; Beef